Equipes de trabalho na administração municipal: a captação de recursos para o desenvolvimento no município de Natividade/RJ - Ribeiro, Roberta Rodrigues (2014)
This thesis aims to identify how teams of at job municipality Natividade influence in raising funds through projects. Was employed research descriptive, explanatory literature and content analysis focused on a qualitative approach, which led to the interpretation of elements detected in field research, aligning them with researched theoretical material . The survey results indicate that the municipal administrators in their departments work of non-integrated form, complicating and compromising the execution of agreements and contracts and causing delays in the progress of processes. It was found that it is necessary investment in technical training, preventive actions and daily monitoring, targeting the correct fulfillment of the requirements for capturing public resources. It is essential to adopt the merit of legitimacy organizational as a mechanism to be able to retain, develop, attract and motivate city officials to work in Project Teams. The main contributions of this study are to provoke reflections on the dynamics of raising public resources for development projects and programs. Was identified a lack of trained technicians and municipal managers to present suitable projects, to identify problems in the implementation of agreements and correct irregularities pointed out in the Ancillary Service Information for Voluntary Transfers - Cauc. It was found that managerial failure causes impacts both in teams of job, as in the progress of the municipality. Keywords: work teams, fundraising, projects.